Autonomy in Classroom Assessment: Teachers' Perceptions on the Abolition of Level 1 Biennials Examinations in Malaysian National Schools - Isa, Anniliza Mohd; Mydin, Al-Amin; Abdullah, Abdul Ghani Kanesan (Secholian Publication PLT, 2022)
Classroom assessment requires teachers to focus their autonomy optimally in assessment without having to be distracted by other forms of assessment, especially among level 1 teachers in primary schools in Malaysia. Three objectives of the study were set; to identify whether teachers are still conducting mid-year and end-of-year examinations for level 1 students, to identify support for the abolition of examinations for level 1 students and to identify increased autonomy in classroom assessment. The quantitative approach was used with survey method as a data collection technique and conducted using an online questionnaire instrument. A total of 662 teachers teaching at level 1 were selected using stratified random sampling. Data were then analyzed using IBM SPSS version 25 descriptively. The findings of the study showed that teachers felt an increase in autonomy in classroom assessment as well as supporting the abolition of examinations for level 1 students. However, the majority of teachers still conduct biennial examinations as part of the assessment.